Galvanic replacement synthesis of AgxAu1−x@CeO2 (0 ≤ x ≤ 1) core@shell nanospheres with greatly enhanced catalytic performance. Issue 12 (16th September 2015) - Liu, Dapeng; Li, Wang; Feng, Xilan; Zhang, Yu
Abstract : A galvanic replacement strategy has been successfully adopted to design Ag x Au1− x @CeO2 core@shell nanospheres derived from Ag@CeO2 ones. Abstract : A galvanic replacement strategy has been successfully adopted to design Ag x Au1− x @CeO2 core@shell nanospheres derived from Ag@CeO2 ones. After etching using HAuCl4, the Ag core was in situ replaced with Ag x Au1− x alloy nanoframes, and void spaces were left under the CeO2 shell. Among the as-prepared Ag x Au1− x @CeO2 catalysts, Ag0.64 Au0.36 @CeO2 shows the optimal catalytic performance, whose catalytic efficiency reaches even 2.5 times higher than our previously reported Pt@CeO2 nanospheres in the catalytic reduction of 4-nitrophenol (4-NP) by ammonia borane (AB). Besides, Ag0.64 Au0.36 @CeO2 also exhibits a much lower 100% conversion temperature of 120 °C for catalytic CO oxidation compared with the other samples.